Sejarah Dan Perkembangan Yayasan United Islamic Cultural Centre Of Indonesia (UICCI) Syarief Medan Tahun 2013- 2023 - Rizaul Abror Siregar; Laila Rohani (Jurnal Budi Pekerti Agama Islam, 2024)
The United Islamic Cultural Center of Indonesia (UICCI) or the United Islamic Cultural Center Foundation in Indonesia is an Islamic organization that operates in the social and religious fields. This foundation is an Islamic social and religious institution that produces Al-Quran Hafiz who applies the Al-Quran and Sunnah in everyday life while directing them to do good deeds with their knowledge. The UICCI Foundation is better known as Pondok Pesantren Syarief Medan which is a branch of the IFA (International Fratenity Association) or international fraternity foundation in Turkey. The history of the founding of the Central UICCI Foundation in Turkey or the Sulaimaniyah Institute began after the fall of the Ottoman Caliphate in 1924, the Turkish regime under the leadership of the nationalist figure Mustofa Kemal Attaturk began to introduce the ideas of nationalism and secularism, or rather laicism. This is an interesting study considering that Islamic boarding schools are traditional Islamic educational institutions originating from Indonesia and UICCI is a branch of Islamic education from Turkey. Because it is a branch of the Turkish Islamic boarding school, it has its own way of learning which is different from Islamic boarding schools in Indonesia in general. The differences lie in the teaching system which is controlled by the center in Turkey, the rules are based on Sufism, the students' learning activities are integrated with the Turkish language, Turkish culture is introduced to the students and the full scholarship for further education in Turkey is given to the students. In this research there are three problem formulations, namely: History and development of the UICCI Syarief Medan Foundation, dynamics, and its contribution to students and society. The approach used by researchers is Sociology. The theory used is Continuity and Change by Jhon Obert Voll. The method used is the historical method, which includes four steps, namely heuristics, verification, interpretation and historiography. The results of this research show that the UICCI Syarief Islamic Boarding School in Medan has a distinctive form and is different from Islamic boarding schools in general. The differences can be seen from the activities at the boarding school which are based on Sufism and tarekat which are followed by Islamic boarding school students, an integrated teaching system with Turkish language and Tekamul education (scholarships for further Islamic education to Turkey). Apart from that, the dynamics that occur at the UICCI Syarief Islamic boarding school can be seen from an educational and economic perspective, namely making UICCI Syarief become the center of Tadris for the Sumatra Island branch and from an economic perspective it can be seen from what was initially free to paid. In terms of contribution, this foundation only focuses on students, preparing student go to Tekamul.